2020
DOI: 10.3389/fphar.2020.01008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hippocampal GABAergic Neurotransmission and Gephyrin Levels by Dihydromyricetin Improves Anxiety

Abstract: Anxiety disorders are the most common mental illness in the U.S. and are estimated to consume one-third of the country's mental health spending. Although anxiolytic therapies are available, many patients exhibit treatment-resistance, relapse, or substantial side effects. An urgent need exists to explore the underlying mechanisms of chronic anxiety and to develop alternative therapies. Presently, we identified dihydromyricetin (DHM), a flavonoid that has anxiolytic properties in a mouse model of isolation-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…Finally, GABAergic markers correlated with anxiety-like behaviors exclusively, and were again stronger correlated in males than females. Such changes in the GABAergic system and their link to anxiety-like behaviors are consistent with previous finding, where reduced GPHN levels in the hippocampus are proposed to contribute to anxiety-like phenotype [79, 80]. Similarly, loss of GAD67 function in particular in SST cells is proposed to contribute to anxiety-like phenotype[81] and reduced levels of GAD are reported in human MDD with comorbid anxiety disorders[82, 83].…”
Section: Discussionsupporting
confidence: 89%
“…Finally, GABAergic markers correlated with anxiety-like behaviors exclusively, and were again stronger correlated in males than females. Such changes in the GABAergic system and their link to anxiety-like behaviors are consistent with previous finding, where reduced GPHN levels in the hippocampus are proposed to contribute to anxiety-like phenotype [79, 80]. Similarly, loss of GAD67 function in particular in SST cells is proposed to contribute to anxiety-like phenotype[81] and reduced levels of GAD are reported in human MDD with comorbid anxiety disorders[82, 83].…”
Section: Discussionsupporting
confidence: 89%
“…Mounting evidence has indicated the critical role of GABA transmission in the progression of anxiety disorder (40). In our previous study, we found that changes in gephyrin expression could re ect changes in GABA A R amount and GABAergic function (10,33). Additionally, we found a reduction in GABA A Rmediated extra-synaptic, pre-, and post-synaptic tonic currents in the social isolation anxiety model, which was restored after DHM treatment (33).…”
Section: Discussionmentioning
confidence: 56%
“…In our previous study, we found that changes in gephyrin expression could re ect changes in GABA A R amount and GABAergic function (10,33). Additionally, we found a reduction in GABA A Rmediated extra-synaptic, pre-, and post-synaptic tonic currents in the social isolation anxiety model, which was restored after DHM treatment (33). To elucidate the mechanism in which DHM modulates GABA A Rs in the socially isolated model, gephyrin protein expression was assessed utilizing Western blot.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using a mouse model of social isolation stress, we examined social isolation stress induced anxiety levels and the effects of DHM with the elevated plus-maze (EPM) and open field (OF) tests [ 31 33 ]. Group-housed control mice (G2 + Veh2) spent 2.31 ± 0.27 (min) of a total 5 min in open arms of the elevated plus-maze (Fig.…”
Section: Resultsmentioning
confidence: 99%